Stranou zájmu pod státním dohledem. Vznik a proměny někdejší vrchnostenské budovy v Malešicích - Vašek, Jan (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2023)
The aim of the study was to cast light on history of central edifice of Malešice manor, until now rather unclear. Inevitably, its story has to begin by the description of the initial purpose of construction at the end of the 17th century, followed by later transformations covering up the former role of the building. A closer look at individual periods of the edifice's history needed to be placed in a context and linked with historical events impacting significantly not only the execution of property rights, but also the physical aspect of the building and connected properties. The development showed, at the beginning, usual characteristics of the nobility administration. However, specific relation between new owner, Charles University, secular faculties respectively, and changing state administration bodies developed by the 18 century. State administration managed to execute successfully their strong influence on decisions concerning as the University real estate, as its metamorphoses motivated by the instantaneous decisions guided by financial interests only, without consideration of potential future impact. This document is therefore focused on this exceptional example of early modern-aged nobility administration, responding to the privileged status of the University and suffocated by state...
Keywords: Malešice-dějiny|Malešice-správní budova statku|vrchnostenská správa|Nové Město pražské|Karlova univerzita|Jan Beck|Vratislavové z Mitrovic|správa státních statků; Malešice-history|Malešice-house of seigneurial administration|seigneurial administration|New Town of Prague|Johann Beck|family Wratislaw of Mitrovitz|administration of state estates